A longitudinal study of age‐related changes in Haemoproteus infection in a passerine bird. Issue 8 (22nd December 2015) - Marzal, Alfonso; Balbontín, Javier; Reviriego, Maribel; García‐Longoria, Luz; Relinque, Carmen; Hermosell, Ignacio G.; Magallanes, Sergio; López‐Calderón, Cosme; de Lope, Florentino; Møller, Anders Pape
Abstract : Blood parasites such as malaria and related haemosporidians commonly infect vertebrate species including birds. Understanding age‐specific patterns of parasite infections is crucial for quantifying the fitness consequences of parasitism for hosts and for understanding parasite transmission dynamics. We analyzed longitudinal and cross‐sectional infection data in house martins Delichon urbica, a migratory bird suffering from intense haemosporidian infection. We separated within‐ from among‐individual effects of age on prevalence. Our results showed that the probability of blood parasite infection increased as individual house martins aged. We also showed that the prevalence of infection decreased with age at last reproduction when controlling for age, showing a selective disappearance of infected birds from the population (i.e. selection). The estimated effect of age on prevalence was underestimated two‐ to three‐fold if not accounting for such selection. This study highlights the importance of taking among‐individual heterogeneity in the capacity to fight a disease into account because such heterogeneity can mask age‐related patterns of infection. These findings emphasize the relevance of considering within‐ and among‐individual patterns of infection in order to understand parasite‐induced mortality and the potential for parasite transmission.